Case Report: Trastuzumab deruxtecan plus toripalimab in ERBB2-amplified cervical mucosal melanoma - Wang, Xiao-Xia; Wang, Min-Xin; Sui, Chao (Frontiers in Oncology, 2025)
Cervical mucosal melanoma is a rare, aggressive malignancy with poor prognosis due to delayed diagnosis and limited treatment efficacy. Current therapies, including immune checkpoint inhibitors (e.g., anti-PD-1 agents), chemotherapy, and targeted therapies, yield suboptimal response rates (<30%) and frequent resistance. Here, we report the first case of HER2-positive cervical mucosal melanoma successfully treated with T-DXd combined with Toripalimab. This combination induced significant tumor shrinkage (partial response) and demonstrated safety, highlighting the potential of ADC-based cross-tumor therapies and immune-targeted synergy. These findings support further clinical trials to validate this strategy in mucosal melanoma, addressing unmet needs in this refractory subtype.